2017
DOI: 10.1016/j.ultrasmedbio.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Investigation into the Use of an Anthropomorphic Breast Sonography Phantom as a Training and Assessment Tool

Abstract: A device for the training and quantitative assessment of the competency of trainee radiologists in the technically challenging area of breast sonography was developed and evaluated. Currently, suitable commercially available devices are lacking, and there is a growing realization that the reliance on direct exposure to patients for learning may not represent best practice from either the trainees' or patients' perspective. Three devices (PI, PII and PIII) were designed to produce very realistic sonographic ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The measurement of the Hounsfield number was performed using a 64-slice CT scanner (Sensation, Siemens Medical Solutions, Karlsruhe, Germany). HU were measured at 80 kVp, with a pixel size of 0.97 × 0.97 mm 2 . In order to maintain HU consistency, the scanner was calibrated using a phantom made of different reference materials with known attenuation coefficients, provided by the manufacturer.…”
Section: Characterization Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of the Hounsfield number was performed using a 64-slice CT scanner (Sensation, Siemens Medical Solutions, Karlsruhe, Germany). HU were measured at 80 kVp, with a pixel size of 0.97 × 0.97 mm 2 . In order to maintain HU consistency, the scanner was calibrated using a phantom made of different reference materials with known attenuation coefficients, provided by the manufacturer.…”
Section: Characterization Protocolsmentioning
confidence: 99%
“…For example, they can be used as tools in operator training for imaging or image-guided interventional procedures. They also represent a quality assessment and image optimization device for the initial implementation of an imaging protocol, and can be used for routine quality control of the same image modality to ensure that the scanning system is operating properly [2]. The use of anthropomorphic phantoms, with a high degree of anatomical, morphological and even pathological realism, is critical to ensure that these features are assessed in a realistically challenging scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Browne et al [12] developed and evaluated sonography phantoms for the training and quantitative assessment of breast sonography. Different designs were used to create realistic sonograph-ic images of breast morphology with a range of embedded pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…The simulation training workshop was carried out over a block of 3 hours, chosen in part to facilitate the recruitment of radiology residents, but also because this time duration was found, in a meta-analysis of 63 studies performed by Donovan & Radosevich, 1999, to be the optimum set-up and practice time for learning complex skills such as ultrasound imaging (18); this meta-analysis revealed that the effect of training intervention over a distributed practice schedule diminished with increased task complexity and increasing time interval between practice sessions. The ultrasound scanning skills which were being developed and assessed through the simulation training workshop in this study were complex, and so it was hypothesised that the approach of a massed training session would provide the best results compared to distributed practice which was how our previous study was carried out (19).…”
Section: Discussionmentioning
confidence: 99%